ASTRONAUT Study: Aliskiren Does Not Improve Postdischarge Outcomes in Patients Hospitalized for Chronic Heart Failure - Kuznar, Wayne (MD Conference Express, 2013)
Aliskiren in addition to standard therapy does not reduce cardiovascular death or heart failure (HF) rehospitalization in patients hospitalized for HF with reduced left ventricular ejection fraction. This article presents data from the Six Months Efficacy and Safety of Aliskiren Therapy on Top of Standard Therapy, on Morbidity and Mortality in Patients With Acute Decompensated Heart Failure trial [ASTRONAUT; Gheorghiade M et al. JAMA 2013].